Spain : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper and Statistical Appendix constructs an index of human capital for the Spanish labor force over 1977-97, and projects it over the next decade on the basis of likely demographic developments. The methodology by which the index is constructed considers both educational attainments resulting from formal schooling and improvements in workers' productivity resulting from experience, or 'learning by doing.' The results suggest that the gains from increases in formal schooling can be large, although they are translated into higher economic growth only gradually.